Clinical review: flow cytometry perspectives in the ICU - from diagnosis of infection to monitoring of injury-induced immune dysfunctions - Venet, Fabienne (BioMed Central, 2011)
Septic syndromes represent a major healthcare problem worldwide. Clinical and experimental evidence indicates that septic patients rapidly present with numerous compromised immune functions. Although flow cytometry remains a relatively confidential diagnostic tool, it could be useful at every step of ICU patient management. Indeed, neutrophil CD64 expression is a sensitive and specific tool for diagnosis of sepsis in adults, neonates and children. Diminished monocyte HLA-DR expression is a reliable marker for the development of monocyte anergy, prediction of secondary nosocomial infection and death in critically ill patients. Finally, the measurement of an increased CD4(+)CD25(+)CD127(low )regulatory T-cell percentage may represent a reliable marker for the diagnosis of lymphocyte dysfunctions in these patients. Ideally, these biomarkers should be part of a panel helping to define ICU patients' immune status. The potential of flow cytometry is further illustrated by use of the biomarkers listed above as stratification tools in preliminary clinical studies. Importantly, many other markers of immune dysfunctions are currently under development that could further enable the administration of targeted individualized therapy in ICU patients. The next critical step would be to use these standardized flow cytometry protocols in large multicentric clinical trials testing individualized immunotherapy.